Pemberdayan Ekonomi Petani Lele Dalam Menuju Ikon Desa Lele (Kasus Desa Senggowar, Kec. Gondang) Kabupaten Nganjuk - Nugrono, Sigit Dwi; Purwadi, Purwadi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Senggowar Village is a part of Gondang sub-district, Nganjuk district, a village that wishes to become a village with a ?catfish? icon. Economic problems cause many parents to work outside the home, so that their children are less attention and get along with the environment that is not true. Some people work in agriculture as agricultural laborers, especially primary products with inadequate income. Village officials and community leaders look for solutions in various opportunities by introducing villages with the icon "Lele Village". Because Catfish is now an animal necessity at a price that is quite affordable by the wider community. The Village Government formed 2 Farmer Groups namely: Mina Tirta 1 and Mina Tirta 2. The activities of these farmer groups are still limited to exhibition activities held by the Nganjuk District Government related to village potential. Sustainability activities have not been carried out optimally, due to the limited knowledge and technology of the community about catfish cultivation and diversification of food made from raw catfish. For this reason, a program of activities for the "Lele Village" was considered. The solution offered by making artificial ponds with tarpaulins that can be done in a narrow yard. Post-harvest handling of processed products from catfish include: Abon Catfish, Catfish Meatballs, Catfish Chips, Catfish Flour, Catfish Dumplings. Marketing with an online model, accounting books, and empowerment of farmer group cooperatives.